Simultaneous multichannel cardiac mapping systems. - Ideker RE; Smith WM; Wolf P; Danieley ND; Bartram FR (Pacing & Clinical Electrophysiology, 1987)
There is much current interest in simultaneous multichannel cardiac mapping. In this paper we give recommendations for the construction of a cardiac mapping system. Because the field of cardiac mapping is relatively young. optimum mapping techniques and all possible applications have not yet been developed. Therefore, the mapping system should be flexible and it should have many capabilities. The system should be digital; if variable gains are used, the amplifiers should be programmable and controlled by a microprocessor. It should be possible to analyze previous recordings and acquire additional recordings simultaneously. The mapping system should be able to record continuously for at least tens of minutes and preferably for hours. The recorded data stream should be a self-contained unit. holding all important electrophysiologic information as well as the recorded electrode signals. The programs should be written in c under a UNIX operating system. A minimum of 64 channels should be used for epicardial or endocardial mapping and a minimum of 128 channels for three-dimensional intramural mapping. The leakage current requirements for multi-channel mapping systems are too stringent and should be re-evaluated. The major limitation to progress in cardiac mapping is neither the hardware nor the software; it is the electrode: its construction, its placement, its fixation, and the interpretation of its recordings.